Meditations - Aurelius, Marcus (London Penguin, 2014)
Originally written only for his personal consumption, Marcus Aurelius's Meditations has become a key text in the understanding of Roman Stoic philosophy. This Penguin Classics edition is translated with notes by Martin Hammond and an introduction by Diskin Clay.
Includes bibliographical references and index.
Keywords: Ethics -- Early works to 1800; Conduct of life -- Early works to 1800